PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KINERJA GURU DAN BUDAYA SEKOLAH TERHADAP MUTU SEKOLAH PADA SMP DI KECAMATAN KERTEK KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to describe The influence of the headmaster’s leadership, teacher’s performance, and school culture to wards school quality of junior high school in Kertek subdistrict Wonosobo Regency, for public and private schools in 2014/2015 academic year.This research was quantitative study that explains of phenomenon of research based on the fact that measured quantitative data. The data were taken from the population of junior high school teachers in Kertek Wonosobo, Central Java. The sample of  research was taken by using proportionale  random sampling technique.  The data collection is managed using questionnaire instruments. These data were analysed using multiple regression analysis with three predictors. The hypotheses tests were handled using F-test or ANOVA and using partial test (t-test) respectively. The data were tested using the prerequisite test. They were normality test, linearity test and multicollinearity test with a significance         level 5 %.Based on the  results of the study, the writer may conclude that, (1) the headmaster’s leadership, teacher’s performance, and school culture have a positive effect on school quality of junior high school in kertek subdistrict wonosobo regency, (2) partially the headmaster’s leadership has a positive effect  on school quality of junior high school in kertek subdistrict wonosobo regency (3) partially teacher’s performance, has a positive effect on school quality of junior high school in kertek subdistrict wonosobo regency (4) partially school culture on has a positive effect school quality of junior high school in kertek subdistrict wonosobo regency. Collectively  the effective contribution percentage’s  67,7 %. Partially the effective  contribution percentage of, (1) the headmaster’s leadership on school quality is 19,082 % (2) teacher’s performance on school quality is 35,445%  and school culture on school quality is 13,154 %